1981
DOI: 10.1002/pssb.2221050156
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Absorption of GaSe Crystals in the Indirect Transition Region

Abstract: GaSe crystals belonging to A%" semiconductor compounds have layer structure /l/. Such crystals are characterized by a strong covalent bond in the layers and a weak van der Waals bond between them. Their optical axis is directed perpendicular to the layers.According to recent calculations of the band structure of GaSe /2/, both direct and indirect transitions with formation of exciton states can occur in such crystals. The difference between their energetic positions is less than 0.1 eV. In accordance with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The energetic position of the band and also a strong polarization dependence of its intensity suggest that the band is due t o the radiative decay of an indirect exciton with emission of one TO phonon, and the band a t 2.008 eV with emission of two TO phonons of 29 meV. This is in agreement with our energy values of an indirect exciton 2.069 eV [8].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The energetic position of the band and also a strong polarization dependence of its intensity suggest that the band is due t o the radiative decay of an indirect exciton with emission of one TO phonon, and the band a t 2.008 eV with emission of two TO phonons of 29 meV. This is in agreement with our energy values of an indirect exciton 2.069 eV [8].…”
Section: Resultssupporting
confidence: 89%
“…Until recently no conclusive evidence on the energet,ic position of the excitons corresponding to indirect transitions has been reported in the literature. It was shown [7] that the shape of the emission spectrum strongly depends on the concentration of structural defects, the number of which can be decreased by doping GaSe with impurities of the F e group We investigated the nature of narrow lines and wide bands of the luminescence spectra of GaSe a t different temperatures and in polarized light taking into account the data on the energy spectrum of an indirect exciton [8]. The number of structural defects in the crystals was considerably decreased by doping with 0.001 wtyo Go.…”
Section: Introductionmentioning
confidence: 99%
“…%) increases slowly together with photon energy, from 6 × 10 3 to 4 × 10 4 cm −1 . The comparison with the results of previous research reported in [40] demonstrates that the spectral distribution of the absorption coefficient in the depth of the fundamental absorption band of GaSe single crystals weakly depends on the presence of Eu, for moderate concentrations. Figure 8a shows the PL spectrum of the single crystalline GaSe plate, which reveals that upon 405 nm excitation, a band with a narrow contoured and maximum peak located at 620 nm (2.00 eV) is formed.…”
Section: Resultssupporting
confidence: 69%
“…As can be seen from the AFM image (Figure 6b), β-Ga2O3:Eu formations are tower-and cone-shaped and exhibit submicrometric bases. The fundamental absorption edge of ε-GaSe single crystals is well studied and is determined by the excitonic absorption mechanism [38][39][40]. The absorption coefficient (α) of radiation with wavelength λ, in both specially undoped and 3.00 at.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation